2006
DOI: 10.1186/1748-717x-1-36
|View full text |Cite
|
Sign up to set email alerts
|

Novel low-kVp beamlet system for choroidal melanoma

Abstract: Background: Treatment of choroidal melanoma with radiation often involves placement of customized brachytherapy eye-plaques. However, the dosimetric properties inherent in sourcebased radiotherapy preclude facile dose optimization to critical ocular structures. Consequently, we have constructed a novel system for utilizing small beam low-energy radiation delivery, the Beamlet Low-kVp X-ray, or "BLOKX" system. This technique relies on an isocentric rotational approach to deliver dose to target volumes within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For example, some reported average dose, some point dose. Esquivel et al 8 and Thomson et al 42 did not show DVH, and Lesperance et al 34 only showed the DVHs of the tumor and lens. Some relevant points of the studies are discussed in the remarks of Tables V and VI.…”
Section: B Comparison To Previous Publicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, some reported average dose, some point dose. Esquivel et al 8 and Thomson et al 42 did not show DVH, and Lesperance et al 34 only showed the DVHs of the tumor and lens. Some relevant points of the studies are discussed in the remarks of Tables V and VI.…”
Section: B Comparison To Previous Publicationsmentioning
confidence: 96%
“…We compared our simulation results of choroid melanoma treatment to Esquivel et al 8 and Lesperance et al 34 in FIG. 11.…”
Section: B Comparison To Previous Publicationsmentioning
confidence: 99%
“…Iwamoto et al 42 have reported on the treatment of canine brain tumors using kilovoltage x rays from a modified computed tomography scanner. Also, the theoretical work of Esquivel et al 43 highlights a novel small beamlet system using an isocentrically mounted x-ray tube operating at 70 kVp for the treatment of ocular disease. The experimental validation of such irradiation devices could make use of a dose imaging system proven to resolve steep dose gradients at the micron level.…”
Section: Discussionmentioning
confidence: 99%
“…The investigated radiotherapy sources included:I-125 and Pd-103, chosen as typical low energy plaque brachy-therapy sources described in TG-43, the Oraya Therapy system with100 kVp energies [14], and the Beamlet Low-kVp X-ray (BLOKX)system with 90 kVp beams [7], developed specifically for treating ocular diseases. The SpekCalc program was used to generate the external energy spectra for the external beam sources, as in previous studies [6][15].…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that, AuNPs could provide a major localized dose enhancement to the diseased endothelial cell (EC) during Oraya therapy. In another study, Monte Carlo radiation transport simulation was used to investigate the use of a small collimated external beam of low energy x-rays (BLOKX system) for the treatment of medium size CM and it was shown that this system can deliver a more conformal dose to the tumor site in comparison to standard plaque therapy [7]. …”
Section: Introductionmentioning
confidence: 99%